The Use of Microwave Derived Activated Carbon for Removal of Heavy Metal in Aqueous Solution - Wahi, Rafeah; Senghie, Herman (Penerbit UTHM, 2011)
Palm oil processing waste which is palm oil kernel shell (POKS) was converted to activated carbon (POKS AC) through 7 min microwave pyrolysis at temperature 270 °C followed by chemical activation using NaOH and HCl. The adsorption study on Ni(II), Cu(II) and Cr(IV) was conducted to evaluate the efficiency of the prepared activated carbon to remove heavy metal. The adsorption capacity was determined as a function of adsorbate initial concentration and adsorbent dosage. Based on Langmuir isotherm, Ni(II) showed highest adsorption capacity of 40.98 mg/g, followed by Cr(IV) and Cu(II) with adsorption capacity of 40.60 mg/g and 13.69 mg/g, respectively. Cr(IV) and Cu(II) showed better fitting to Freundlich isotherm model with high correlation regression indicating the applicability of heterogeneous adsorption. Ni(II) show better fitting with Langmuir isotherm that indicate monolayer coverage. The use of POKS AC is not only effective for adsorption of Cr(IV), Ni(II) and Cu(II) in aqueous solution but also helps to overcome the over abundance of POKS waste problem.